ANALISIS TERHADAP BADAN PENYELENGGARA JAMINAN SOSIAL (BPJS): TRANSFORMASI PADA BUMN PENYELENGGARA JAMINAN SOSIAL - Nidya Waras Sayekti; Yuni Sudarwati (Jurnal Ekonomi & Kebijakan Publik, 2010)
The National Social Security System Act (NSSS Act) mandated the establishment of BPJS as the operator of national social security system. Nevertheless a lot of pro’s and con’s came up. Some argue that BPJS can be formed from temporary BPJS i.e. PT. Jamsostek, PT. Askes, PT Asabri and PT. Taspen. While some others argue that the four BUMN are not feasible to be BPJS because they are in the form of Limited Company. This essay aims to find the best form of BPJS as mandated by NSSS act. The result of the study shows that at present there has not been any governmental agency appropriate as mandated by NSSS Act. The best way in order to bring into reality BPJS is by transforming the four already available BPJS.